CXCL12/CXCR4 activation by cancer‐associated fibroblasts promotes integrin β1 clustering and invasiveness in gastric cancer. Issue 5 (9th October 2015) - Izumi, Daisuke; Ishimoto, Takatsugu; Miyake, Keisuke; Sugihara, Hidetaka; Eto, Kojiro; Sawayama, Hiroshi; Yasuda, Tadahito; Kiyozumi, Yuki; Kaida, Takayoshi; Kurashige, Junji; Imamura, Yu; Hiyoshi, Yukiharu; et al.
Abstract : Cancer‐associated fibroblasts (CAFs) are reportedly involved in invasion and metastasis in several types of cancer, including gastric cancer (GC), through the stimulation of CXCL12/CXCR4 signaling. However, the mechanisms underlying these tumor‐promoting effects are not well understood, which limits the potential to develop therapeutic targets against CAF‐mediated CXCL12/CXCR4 signaling. CXCL12 expression was analyzed in resected GC tissues from 110 patients by immunohistochemistry (IHC). We established primary cultures of normal fibroblasts (NFs) and CAFs from the GC tissues and examined the functional differences between these primary fibroblasts using co‐culture assays with GC cell lines. We evaluated the efficacy of a CXCR4 antagonist (AMD3100) and a FAK inhibitor (PF‐573, 228) on the invasive ability of GC cells. High CXCL12 expression levels were significantly associated with larger tumor size, increased tumor depth, lymphatic invasion and poor prognosis in GC. CXCL12/CXCR4 activation by CAFs mediated integrin β1 clustering at the cell surface and promoted the invasive ability of GC cells. Notably, AMD3100 was more efficient than PF‐573, 228 at inhibiting GC cell invasion through the suppression of integrin β1/FAK signaling. These results suggest that CXCL12 derived from CAFs promotes GC cell invasion by enhancing the clustering of integrin β1 in GC cells, resulting in GC progression. Taken together, the inhibition of CXCL12/CXCR4 signaling in GC cells may be a promising therapeutic strategy against GC cell invasion. Abstract : What's new? The presence in the tumor stroma of cancer‐associated fibroblasts (CAFs) may be an indication of imminent tumor invasion and metastasis. CAFs appear to function through the stimulation of CXCL12/CXCR4 signaling, though precisely how these chemokines contribute to cancer progression is uncertain. Here, in gastric cancer cells, CXCL12/CXCR4 activation by CAF2 was found to enhance the clustering of integrin β1 at the cell surface and thereby promote gastric cancer cell invasiveness and motility. Increased invasiveness was suppressed by treatment with the CXCR4 antagonist, AMD3100, which blocked interactions between integrin β1 and the extracellular matrix.